Rekonstruksi Nilai-Nilai Qur’ani sebagai Paradigma Etika Ekologis Islam dalam Menjawab Krisis Lingkungan Global: Rekonstruksi Nilai-Nilai Qur’ani sebagai Paradigma Etika Ekologis Islam dalam Menjawab Krisis Lingkungan Global - Ayub Kumalla; Darul Mustofa; Desta Tri Wahyuni; Zulhannan; Ali Murtadh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT The global environmental crisis, marked by climate change, ecosystem degradation, and excessive exploitation of natural resources, has become a serious challenge for human civilization. In the context of Islam, the Qur’an as the primary source of law contains a set of moral and spiritual values that can serve as the foundation for ecological ethics. This article aims to reconstruct Qur’anic values relevant to environmental ethics and offer them as an alternative paradigm in addressing the contemporary ecological crisis. The research method employed is a conceptual literature review, examining ayat kauniyah (verses of nature), classical and contemporary exegesis, as well as scientific literature related to Islamic ecological theology. The study reveals that Qur’anic principles such as tawhid (cosmic unity), khalifah fi al-ard (human responsibility as stewards of the earth), mizan (balance), and amanah (moral trust) form the basis of a holistic and sustainable ecological ethic. By revitalizing these values, the paradigm of Islamic ecological ethics can significantly contribute to fostering spiritual awareness of environmental preservation and provide new direction for the global discourse on environmental ethics.